5)
The x-values go up by 1: -2, -1, 0, 1, 2
The y values are always 3 times the previous value.
This is an exponential function.
![y = a(b)^x](https://tex.z-dn.net/?f=%20y%20%3D%20a%28b%29%5Ex%20)
We need to find a and b.
Look at x = 0.
For x = 0, y = 4.
![y = a(b)^x](https://tex.z-dn.net/?f=%20y%20%3D%20a%28b%29%5Ex%20)
![4 = a(b)^0](https://tex.z-dn.net/?f=%204%20%3D%20a%28b%29%5E0%20)
Since b^0 = 1, this simplifies to
![4 = a](https://tex.z-dn.net/?f=%204%20%3D%20a%20)
Now we know a = 4. We have
![y = 4(b)^x](https://tex.z-dn.net/?f=%20y%20%3D%204%28b%29%5Ex%20)
Look at x = 1. For x = 1, y = 12.
![12 = 4(b)^1](https://tex.z-dn.net/?f=%2012%20%3D%204%28b%29%5E1%20)
![12 = 4b](https://tex.z-dn.net/?f=%2012%20%3D%204b%20)
![b = 3](https://tex.z-dn.net/?f=%20b%20%3D%203%20)
Now that we know a and b, we can write the function.
![y = 4(3)^x](https://tex.z-dn.net/?f=%20y%20%3D%204%283%29%5Ex%20)
Now that you have the function written out, notice the following.
In the exponential equation we found, the number raised to x
is the number you multiply each y value to get the next y value.
In this case, each y value is 3 times the previous one, so you have 3^x.
The way you find "a" in the exponential equation is to look at the y-coordinate
when x = 0. When x = 0, b^x is 1, so b^x drops out, and you get "a" equal to
the y-value. In this case, when x = 0, y = 4, so "a" is 4.
With b = 3, and a = 4, you can quickly write:
y = 4(3)^x.